Dimorphic Modulation of Immunity: From Gender to Hormones - Ghosh, Dr. Somenath (Asian Journal of Pharmaceutics (AJP), 2018)
The open circuit system of immunity is composed of different cellular and non-cellular components. However, the components are seemingly limited in view of their multifaceted actions. Hence, the particularity and functional diversity of immune system lie in the mode of regulation of all of its components. There are different factors which regulate the proper function and modus operandi of several components of immune system. Among them, one most important factor is regulation through hormones. There are different classes of hormones, but in context of immune system, hormones are immune-enhancing, immune-inhibitory, or immune-neutral. In-depth studies have shown that response of immune system varies with hormones of different kinds. It depends on the context (in vivo and in vitro), nature of hormone (steroid, proteinaceous, peptide, amino acid, and amino acid derivative), body condition (healthy vs. under pathological/clinical), and their behavior when in combination with other hormones and in contact with cellular and non-cellular components of immune system. It is notable that males and females of any animal differ physiologically and one of the reasons behind different physiology is involvement of hormones. Thus, it is a matter of investigation how gender-wise differentiation exists at immunological level. Till date, very little is known in this aspect and in-depth molecular studies are on the way to explore out the reason. This review, however, in brief, encompasses the dimorphism of immunity and immune response in terms of gender under hormonal regulation.